2022
DOI: 10.3389/fped.2021.796426
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic Stem Cell Transplantation in Adolescents and Young Adults With Acute Lymphoblastic Leukaemia: Special Considerations and Challenges

Abstract: Adolescents and young adults (AYAs) represent a challenging group of acute lymphoblastic leukaemia (ALL) patients with specific needs. While there is growing evidence from comparative studies that this age group profits from intensified paediatric-based chemotherapy, the impact and optimal implementation of haematopoietic stem cell transplantation (HSCT) in the overall treatment strategy is less clear. Over recent years, improved survival rates after myeloablative allogeneic HSCT for ALL have been reported sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 107 publications
(221 reference statements)
0
4
0
Order By: Relevance
“…Only 15 (29%) transplanted patients were Ph+ , suggesting that blinatumomab and TKI treatment led to a lasting remission, potentially causing the transplant-sparing effect. This is crucial clinically, as transplantation, a complex procedure, is linked to potential complications [ 28 ]. Blinatumomab might serve as a potential transplantation alternative in Ph+ B-ALL, but further studies are needed to validate our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 (29%) transplanted patients were Ph+ , suggesting that blinatumomab and TKI treatment led to a lasting remission, potentially causing the transplant-sparing effect. This is crucial clinically, as transplantation, a complex procedure, is linked to potential complications [ 28 ]. Blinatumomab might serve as a potential transplantation alternative in Ph+ B-ALL, but further studies are needed to validate our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric protocols, as a rule, include late intensification and early and intensive central nervous system (CNS) prophylaxis. Conversely, adult protocols use more myelosuppressive drugs (like anthracyclines, cyclophosphamides…) and more patients (about 30% of AYA) are transplanted in the first complete remission (CR1), in contrast to less than 5-10% of children in CR1 [5]. Considering this, numerous retrospective, as well as prospective clinical trials were conducted and confirmed the eligibility and improved outcome with the use of pediatric regimens in treating AYA patients [6].…”
Section: Contributing Factors For Different Outcome Between Children ...mentioning
confidence: 99%
“…The risk adapted treatment approach is generally accepted and the risk stratification is based primarily on cytogenetics and minimal/measurable residual disease (MRD). New immunotherapeutic drugs (blinatumomab and inotuzumab ozogamicin), with a proven efficacy in relapsed/refractory patients with ALL, are currently investigated as a part of frontline protocols in order to induce deeper remissions [5].…”
Section: Current Treatment and Novel Approaches In The Treatment Of A...mentioning
confidence: 99%
“…Hematopoietic stem cell transplantation (HSCT) is a curative treatment for patients with hematologic malignancies, including various leukemias and lymphomas, as well as is used in children with high-risk solid tumors [ 1 ]. HSCT is only beneficial for children who have a high risk of relapse from conventional chemotherapy [ 2 ]. Therefore, therapy plans that precisely identify these high-risk patients and perform HSCT when suitable allogeneic donors are available are the preferred treatment for various disorders.…”
Section: Introductionmentioning
confidence: 99%